POSISI KEBERLANJUTAN INDONESIA DALAM PENCAPAIAN SDGs PANGAN DAN PERTANIAN : ANALISIS RAP-SDGs DI ASIA TENGGARA - Tambunan, Varingan Prianando (Jurusan Penyuluhan Pertanian FP UHO, 2026)
The Sustainable Development Goals (SDGs) agenda emphasizes the integration of economic, social, and environmental dimensions in realizing a sustainable food and agricultural system. This study analyzes Indonesia's sustainability position compared to eleven Southeast Asian countries using the RAP-SDGs method based on Multidimensional Scaling (MDS). Secondary data from the FAO SDGs Database for the period 2019–2024 was used to compile a sustainability index, identify leverage indicators through leverage analysis, and evaluate outcome uncertainties through 100 iterations of Monte Carlo simulations. The results showed significant differences between countries, where only Indonesia, Thailand, Timor Leste, and Viet Nam reached the